Maritime Health Literacy Among Cadets: Aligning Education - Hesti Ekawati; Antoni Arif Priadi; Wisnu Handoko; Ahmad Ahmad; Tri Cahyadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research investigates maritime health literacy among cadets, focusing on its alignment with international standards and implications for professional practice in the maritime industry. Using qualitative methods, the study explores cadets' perceptions and experiences regarding health management practices onboard ships. Findings reveal a strong alignment with safety and environmental protocols outlined by the International Maritime Organization (IMO). However, gaps in practical training effectiveness and continual professional development highlight areas for improvement. Cadets express the need for enhanced practical simulations and lifelong learning initiatives to better prepare for health-related challenges at sea. The study also identifies positive perceptions of health promotion policies mandated by the maritime labour convention, underscoring industry commitment to promoting occupational health and safety standards. Recommendations include integrating comprehensive mental health support, fostering collaborative research efforts, and conducting longitudinal studies to assess the sustainability of health literacy interventions. By addressing these recommendations, stakeholders can enhance operational efficiency, promote crew welfare, and sustain a culture of safety within the maritime sector.